The Effect of Risk Perception and Perceived Ease of Use on Intention to Use Dana E-Wallet in Medan City with E-Trust as an Intervening Variable Plantation - Angellia Saragih; Arlina Nurbaity; Beby Karina Fawzeea Sembiring (Indonesian Journal Publisher, 2026)
Advances in information technology have brought significant transformations in digital payment systems, particularly through the adoption of e-wallets as fast, easy, and secure transaction solutions. Medan, as one of Indonesia's metropolitan cities, has witnessed a growing trend in e-wallet usage, especially the DANA application. However, digital payment technology adoption still faces challenges related to risk perception and user trust. This study aims to analyze the influence of risk perception and perceived ease of use on the intention to use the DANA e-wallet in Medan City, with e-trust as an intervening variable. A quantitative approach with an associative research design was employed. The study population consists of DANA e-wallet users in Medan City (total population of 2,474,166 residents), classified as an infinite population. A sample of 165 respondents was selected through purposive sampling, with the criterion of having used DANA at least twice in the past three months. Data were collected through questionnaires distributed at coffee shops across 21 sub-districts (kecamatan) of Medan. Data analysis was performed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with SmartPLS 4. The results indicate that: (1) risk perception has a direct negative and insignificant effect on usage intention; (2) risk perception has a negative and insignificant effect on e-trust; (3) perceived ease of use has a direct positive and significant effect on usage intention; (4) perceived ease of use has a positive and significant effect on e-trust; (5) e-trust has a positive and significant effect on usage intention; (6) e-trust does not mediate the relationship between risk perception and usage intention; and (7) e-trust significantly mediates the relationship between perceived ease of use and usage intention. These findings highlight that ease of use and e-trust are the dominant factors driving DANA e-wallet adoption in Medan City.